Effect of Freewriting and Questioning Brainstorming Instructional Strategies on Junior Secondary School Students’ Learning Outcomes in Basic Science in Osun State, Nigeria (2015)
This study investigated effects of Freewriting Brainstorming Instructional Strategies (FBIS) and Questioning Brainstorming Instructional Strategies (QBIS) on Junior Secondary School (JSS) students’ learning outcomes in Basic Science in Osun State, Nigeria. The moderating effects of gender and personality traits were also examined. The pretest-posttest, control group, quasi experimental design involving 3x2x2 factorial matrix was employed. The research population comprised all the JSS II students in the state. Nine purposively selected state-owned co-educational secondary schools across the three Senatorial districts of the state were involved. Four hundred and fifty JSS II students from intact classes from the schools were used as research sample. The Research instrument were Attitude of Students to Basic Science Scale (Alpha coefficient (∞)=0.89), Students Personality Trait Scale (∞=0.94), Students’ Basic Science Achievement Test (SBAT), Evaluation Sheet for Assessing Teachers’ Performance during Training, and Teachers’ Instructional Guides for FBIS and QBIS. Seven hypotheses were generated and tested at p=0.05. Data were analysed using descriptive statistics, ANCOVA and MCA. The result showed; participants as comprising 217 (48.22%) males and 233 (51.78%) females; that the students were predominantly less than 15years old (87.56%); that the brainstorming strategies had significant effect on the students’ achievement (F (2, 449) = 364.140, p< .05) and attitude (F(2, 449) = 259.381, p < .05) but that personality traits did not have significant effect on the students’ achievement (F (1, 449) = 2.071, p > .05) but had significant effect on the students’ attitude towards Basic Science (F(1, 449) = 29.235, p < .05); that gender had no significant effect the students’ achievement (F(1, 449) = .122, p > .05) and attitude (F(1, 449) = .502,p> .05); that there was a significant interaction effect of the brainstorming strategies and personality traits on the students’ achievements (F(2, 449) = 4.026, p < .05) and attitude (F(2, 449) = 30.281, p < .05); that there was no significant interaction effect of the brainstorming strategies and gender on students’ achievements (F(2, 449) = .676, p > .05) and attitude (F(2, 449) = 2.196, p > .05); that there was no significant interaction effect of gender and personality traits on the students’ achievement (F(1, 449) = .010, p > .05) and attitude (F(2, 449) = 2.263, p > .05) and that there was no significant interaction effects of the brainstorming strategies, personality traits and gender on students’ achievements (F(2, 449) = .741, p > .05) and attitude to Basic Science (F(2, 449) = 1.381, p > .05) and that the Freewriting strategy effected higher improvement in students’ achievement and attitude than the Questioning strategy. It was concluded that the brainstorming instructional strategies enhanced the JSS II students’ achievement and attitude but that the Freewriting strategy was more effective than the Questioning strategy and that low personality trait students (introverts) perform higher but with lower attitude score than the high personality trait students (extroverts). It was recommended that these two strategies be adopted in teaching Basic Science in secondary schools in Osun State.